2017
DOI: 10.1590/1678-4499.505
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo e exportação de macronutrientes em beterraba sob diferentes manejos de fertirrigação e salinidade

Abstract: Fertigation is a major form of fertilizer installments;however, if applied in excess, the fertilizers can damage the crop development. The objective of this study was to evaluate the accumulation and exportation of macronutrients in a beet cultivation under 2 fertigation managements at different levels of soil salinity. ). There was an increased accumulation of nutrients studied for both cultivars and fertigation managements until electrical conductivity levels between 3 (M 1 ) and 6 (M 2 ) dS•m −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 13 publications
(16 reference statements)
3
12
1
2
Order By: Relevance
“…The observed results determined the order of accumulation by beet, with K > N > P > B, in agreement with the findings other authors (SEDIYAMA et al, 2011;CARDOSO et al, 2017;SILVA;SILVA;KLAR, 2017). Of the total accumulated nutrients, the tuberous root participated with 66% of N, 53% of P, 39% of K and 72% of B.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The observed results determined the order of accumulation by beet, with K > N > P > B, in agreement with the findings other authors (SEDIYAMA et al, 2011;CARDOSO et al, 2017;SILVA;SILVA;KLAR, 2017). Of the total accumulated nutrients, the tuberous root participated with 66% of N, 53% of P, 39% of K and 72% of B.…”
Section: Resultssupporting
confidence: 91%
“…In an experiment with the hybrid beet 'Boro', Cardoso et al (2017) observed, at harvest, N total accumulation of 177.3 mg in the shoot and 481.8 mg in the tuberous root. P was accumulated in a smaller amount among macronutrients, in agreement with that observed by Silva, Silva and Klar (2017). K was the nutrient accumulated in greater quantity by the shoot and tuberous root of beet (Table 3), corresponding to a total of 305 kg ha -1 of K and equivalent to 367.5 kg ha -1 of K 2 O.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2A), there was a decrease of 1.14% per unit increase in the electrical conductivity of the water, reduction of 5.81% when compared to the plants irrigated with ECw 0.3 dS m -1 . This fact is possibly promoted by the concentration of salts in the soil solution, which makes it difficult for water to be absorbed by plants due to the greater energy expenditure to maintain its turgidity [21]. Physical and chemical characteristics of the substrate used in the experiment ................................................ Chemical characteristics ............................................... .................................................…”
Section: Resultsmentioning
confidence: 99%
“…Arugula production can be influenced by several factors linked to management strategies, as inappropriate irrigation blade, climate, cultural practices, pest and disease control, and, mainly, availability of nutrient for the plant due to adequate crop fertilization is one of the most important attributes for crop productivity [3]. In this sense, the knowledge of the number of nutrients accumulated in plants enables the adoption of strategies in the crop fertilization program [25].…”
Section: Introductionmentioning
confidence: 99%